From Victim to Villain: Cycling, Traffic Policy, and Spatial Conflicts in Stockholm, circa 1980. Issue 2 (1st June 2019) - Emanuel, Martin
Abstract : This article employs a social practice approach to analyze the boom and bust of cycling in Stockholm around 1980, in the context of broader socioeconomic trends and under the influence of new cyclists, bicycle innovation, and local traffic policy. Within a predominantly car-based city traffic regime, which rendered some mobility practice more legitimate than others, measures intended for cyclists were taken at the expense of pedestrians rather than motorists. Because of a blend of more cyclists, faster bicycles, and design choices based on the car as norm, the image of the cyclist transformed from that of the victim (of automobility) to the villain, and, for this reason, cycling was less easily supported by local politicians. Combined with the second wave of automobility in the 1980s, bicycle policy and planning lost its steam, and cycling declined.